RANCANG BANGUN SISTEM INFORMASI BATAM DIRECTORY MENGGUNAKAN METODE BACKWARD CHAINING BERBASIS MOBILE - Hamsir hamsir; Gunadi W Nurcahyo; Sarjon Defit (Elektron : Jurnal Ilmiah, 2012)
This article is designed for an information system in the form of expert system applications to present information on Batam Directory. The purpose of this system is to help provide information about the city of Batam as a whole to the residents of Batam city in particular and thelocal and foreign tourists as well as prospective investors in general. The system presents information in the form of public service to the residents of Batam city government and other newcomers as well as products and services are made ​​and offered by the business and government. The analysis was done by determining the first goal, then do these arching to obtain the desired information. The design system uses backward chaining inference method to the implementation ofthe system using My-SQL database systems and programming languages​​ of PHP and JQuery. The system is based on mobile, so it can be accessed using a mobile device.